Online condition monitoring of IGBT modules using voltage change rate identification - Pou, Josep (2019)
As insulated gate bipolar transistors (IGBTs) have gained an important status in a wide range of applications, reliability, and availability of these units are of paramount importance to meet stringent requirements spelled in aviation and industrial standards. Reliability of a power converter is mainly verbalized by the failure rate of power modules. Hence, monitoring IGBTs degradation is very crucial to give early sign of power-module-related failures in power converters. This paper proposes a new potential precursor parameter for IGBTs based on voltage change rate to detect early failure of power modules. The proposed method pays more attention to power modules with chip solder fatigue and bond-wire lift off as a major failure mechanism. An experimental setup using an accelerated power cycling machine is constructed to trigger degradations and failures on several IGBT modules. The experimental results indicate that voltage change rates of the IGBT modules decrease with ageing over time. It is found that the local damage induced by ageing over time changes the parasitic capacitances of an IGBT that leads to a decrease of the voltage change rate of the device.